Monitoring And Management Ion Concentrations In The Air Of Industrial And Public Premises - Bolibrukh, Borys; Glyva, Valentyn; Natalia, Kasatkina; Levchenko, Larysa; Tykhenko, Oksana; Panova, Olena; Bogatov, Oleg; Petrunok, Tetiana; Aznaurian, Iryna; Zozulya, Sergey; Aznaurian, Iryna (My University, 2022)
This paper reports a substantiated method and a designed device for controlling the concentrations of air ions in premises in accordance with the European standards SBM 2015. The use of an ultrasonic humidifier with a capacity of 25 W for two hours increases the concentration of negative ions around the device from 240 to 560 cm-3, positive ones ‒ from 260 to 410 cm-3. The intensity of the electrostatic field of a polymeric coating decreases from 5.1 to 0.2 kV/m. The disadvantage of the humidifier is a small radius of influence (1.0–1.5 m) and the inability to control the polarity of ions. It has been experimentally established that air cooling systems (split systems) deionize the air of the premises. Degrees of deionization and dominating polarity are unpredictable and different for devices of different manufacturers and brands. To control the ion composition of the air simultaneously with the maintenance of normative relative humidity and stresses of static fields, the structure was proposed and the effectiveness of a bipolar ultrasonic air ionizer with adjusted performance and dominating polarity has been tested. The maximum productivity of the ionizer is 4,000–5,000 cm-3. The radius of exposure is 5 m (reducing the concentration of ions with a distance to 500 cm-3). To pass the ionized air through an air capacitor, the number and predominant polarity of air ions are regulated by the polarity and voltage on the covers of the capacitor. It was established that in order to service a room with an area of 50 m2, an ultrasonic emitter with a capacity of 25 W would suffice. The adjustability of the device performance makes it possible to reduce or increase the service area. The ability to purify air from suspended particles is shown. During the two hours of operation of the ionizer, the dust content decreased from 4.3–4.4 mg/m3 to 1.4–1.6 mg/m3.
Keywords: air ionization; electrostatic charge; ultrasonic humidifier; triboelectric effect; air purification; microclimate; 628.512